Clustering and visualisation of the GABRIEL network expertise in the field of infectious diseases - Philippe Vanhems; Shally Awasthi; Firdausi Qadri; Sayera Banu; Francine Ntoumi; Graciela Russomando; Jianwei Wang; Zakir Hossain; Bourema Kouriba; Sara Eyangoh; Chan Leakhena Phoeung; Cécile Chauvel; et al. (BMJ Global Health)
Introduction The Global Approach to Biology Research, Infectious diseases and Epidemics in Low-income countries (GABRIEL) network is an international scientific network of 21 centres coordinated by the Merieux Foundation (Lyon, France). Mapping and characterising the similarities and differences in expertise and activities across four major infectious diseases (tuberculosis, antimicrobial-resistant infections, acute respiratory infections and emerging pathogens) among these centres would help to provide a better understanding of the network’s capacity. It will also highlight how the applied methodology can enhance information sharing within research networks.Methods Each centre responded to a questionnaire on their core activities and research themes. An advanced multivariate analysis was performed to relate all items together and highlight new synergies among members of the GABRIEL network. Similarities were found using a clustering algorithm and data were visualised using alluvial plots.Results This strategy enabled to find new patterns in the GABRIEL network for the implementation of new projects on global health, regardless of geographical proximity or historical connections. Five clusters based on core activities, consisting of 6, 1, 3, 9 and 2 research units, respectively, have been identified, with clusters 1 and 4, including the majority of the units. Four clusters have been defined based on the four major infectious diseases, comprising 7, 3, 5 and 6 research units, respectively.Conclusions The same methodology could also be applied to identify proximities on other networks of experts or between members of different networks for more efficient research or surveillance global programmes.